Personal Reflections on Blackfoot Men and Matriculture: Transcript - Cardinal, Douglas (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
In this recorded interview, Douglas Cardinal shares his thoughts on having Blackfoot heritage and what that means, as well as the role of Blackfoot men in the lives of Blackfoot women. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Blackfoot Men and Matriculture, Douglas Cardinal